Deregulated ALG‐2/HEBP2 axis alters microtubule dynamics and mitotic spindle behavior to stimulate cancer development. Issue 11 (1st March 2017) - Qin, Juan; Yang, Yang; Gao, Siqi; Liu, Yang; Yu, Fan; Zhou, Yunqiang; Lyu, Rui; Liu, Min; Liu, Xinqi; Li, Dengwen; Zhou, Jun
Abstract : Cancer cells are characterized by genomic instability, resulting in the accumulation of mutations that promote cancer progression. One way that genomic instability can arise is through improper regulation of the microtubule cytoskeleton that impacts the function of the mitotic spindle. In this study, we have identified a critical role for the interaction between apoptosis‐linked gene 2 (ALG‐2) and heme‐binding protein 2 (HEBP2) in the above processes. Our data show that the gene copy numbers and mRNA levels for both ALG‐2 and HEBP2 are significantly upregulated in breast and lung cancer. Coexpression of ALG‐2 and HEBP2 markedly increases the cytoplasmic pool of ALG‐2 and alters the subcellular distribution of HEBP2. Our data further reveal that abnormality in the ALG‐2/HEBP2 interaction impairs spindle orientation and positioning during mitosis. In addition, this complex appears to modulate the dynamic properties of microtubules in cancer cells. These finding thus uncover an important function for deregulated ALG‐2/HEBP2 axis in cancer development by influencing microtubule dynamics and spindle behavior, providing novel insight into the etiology and pathogenesis of cancer. Abstract : In this study, we uncover a previously unrecognized role for deregulated ALG‐2/HEBP2 axis in cancer development. Mechanistically, this is mediated by altered microtubule dynamics and impaired spindle orientation and positioning.